Struktur, Unsur, dan Tipe Teks dalam Teks Cerita Fantasi Karya Peserta Didik - Erina Novita; Nursaid Nursaid (Faculty of Social Science, Universitas Negeri Padang, 2021)
Fantasy story text is one of the narrative texts that contains events or events that happened to a character being told. The series of events has a plot that starts from orientation, complications, to resolution. Fantasy stories actually also feature realistic events and actions, but there are also things that are hard to accept. Even so, the overall development of the storyline is still subject to the law of cause and effect or the law of the plot that applies in writing that is generally agreed upon. This study aims to determine the tendency of students in making fantasy story texts and this research focuses on elements, structures, and types in fantasy story texts. This research uses qualitative research with descriptive method. The results obtained are that students tend to make fantasy story texts based on examples that have been given. In addition, the structure used tends to be incomplete. In the orientation section is often not used. The type of fantasy story text used tends to cross time. The written message tends to be implicit